MUDAS DE OITI (Licania tomentosa) EM DIFERENTES AMBIENTES E MATERIAL REFLETOR EM BANCADA - ALVES, Vitória Carolina Dantas; MARQUES, Ana Letícia Ribeiro; SOUZA, Larissa Gabriela Pereira de; VIEIRA, Mariane Tavares; COSTA, Edilson (ANAIS DO ENIC, 2020)
-